The effect of six days open water swimming activity on salivary, oxidative stress and cortisol levels on elite master swimmers - Nihal Sekhar Oktay; Kubilay Cimen; Beste Tacal Aslan; Sukriye Caliskan; Cengiz Karagozoglu; Korkut Ulucan (ROL Spor Bilimleri Dergisi)
Open water swimming is a sport and recreational activity in which individuals swim in natural bodies of water. When the body is under stress, stress hormones, and reactive oxygen metabolite production may increase. The study aims to evaluate the effect of swimming stress on oxidation formation, antioxidant response, and cortisol levels in whole saliva samples of long-distance open-water swimmers taken before and after swimming. Lipid peroxidation (LPO), superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), and sialic acid (SA) were determined in the whole saliva of the 12 swimmers before and after swimming. Also, cortisol levels were measured from whole saliva collected in 10 laps, before and after each swim. The salivary LPO level of the swimmers significantly increased, and SOD and CAT activities and SA levels decreased significantly after swimming compared to the baseline. After swimming, the salivary cortisol levels of the swimmers significantly increased in the 1st, 2nd, and 3rd laps of the swim compared to each one’s baseline levels. It was also observed that swimming activity caused an increase in total cortisol levels in all laps compared to baseline swimming. Swimming in open water can cause stress on the organism, leading to metabolic adaptations for prevention.